2019
DOI: 10.1007/s40518-019-00135-2
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and Energy Impacts of Shared Automated Vehicles: a Review of Recent Literature

Abstract: Purpose of Review: The purpose of this review is to present findings from recent research on Shared automated vehicles (SAV) impacts on mobility and energy. Recent Findings: While the literature on potential SAV impacts on travel behavior and the environment is still developing, researchers have suggested that SAVs could reduce transportation costs and incur minimal increases in total trip time due to efficient routing to support pooling. Researchers also speculate that SAVs would result in a 55% reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 39 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…An area where benefits could be significant would be where shared mobility is adopted, particularly where this is coupled with vehicle electrification 30 . Shared mobility reduces the number of vehicles required and subsequently reduces resource demands for the production and maintenance of such vehicles.…”
Section: Energy and The Environmentmentioning
confidence: 99%
“…An area where benefits could be significant would be where shared mobility is adopted, particularly where this is coupled with vehicle electrification 30 . Shared mobility reduces the number of vehicles required and subsequently reduces resource demands for the production and maintenance of such vehicles.…”
Section: Energy and The Environmentmentioning
confidence: 99%
“…Shaheen et al (2015) utilized a microscopic estimation model to analyze the effect of reducing the emissions and energy consumption of autonomous vehicles. They suggested that emissions can be reduced thanks to the platooning of autonomous vehicles [21]. Fangfang et al (2017) analyzed emissions and energy consumption at a signalized intersection.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of research projects on the individual technologies and innovations have been carried out and published. An example from the vast body of literature on this topic is [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%